MODEL OF HISTORY TEACHING BASED ON THE USE OF PRIMARY HISTORICAL SOURCES - Nur Fatah Abidin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
Analyzing primary historical sources become the biggest challenge for students in history class. This research aims to develop EAR learning instruction based on the elaboration of historical thinking and three cognitive processes of knowledge construction. The Elaboration Theory was adopted to calibrate those concepts into systematic learning instruction for analyzing the primary source in history class. The elaboration generates EAR learning instruction consisted of three stages namely Engagement, Anatomization, and Reconstruction. These stages represent systematic steps to sourcing, analyzing, and reconstructing historical narrative based on the analysis of the primary source. EAR learning instruction can provide implementable steps to examine primary historical sources in history class and support the improvement of students’ historical thinking by giving a simple path to analyze the primary historical sources. EAR is expected diminishing students’ barriers in facing complexity in analyzing the primary source in history class.